2011
DOI: 10.1111/j.1365-277x.2011.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

An unblinded randomised controlled trial of preoperative oral supplements in colorectal cancer patients

Abstract: Background:  Perioperative oral supplementation has been shown to reduce post‐operative complications. However, the use of preoperative standard oral supplements in a cohort of colorectal cancer patients has not been evaluated. The present study examined whether preoperative supplements are beneficial in this group. Methods:  In a randomised controlled trial, patients were assigned to receive 400 mL of oral supplement and dietary advice or dietary advice alone. Primary outcome was the number of post‐operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 27 publications
2
80
0
3
Order By: Relevance
“…40 Several past studies have failed to identify a major benefit from the use of standard preoperative ONS. [41][42][43] This might be due to the lack of a clear definition of "malnutrition" and inclusion of wellnourished patients. Adherence to the new definitions of malnutrition, as is being popularized by several societies, 44 may serve to identify which patients will benefit the most from preoperative supplements.…”
Section: Discussionmentioning
confidence: 96%
“…40 Several past studies have failed to identify a major benefit from the use of standard preoperative ONS. [41][42][43] This might be due to the lack of a clear definition of "malnutrition" and inclusion of wellnourished patients. Adherence to the new definitions of malnutrition, as is being popularized by several societies, 44 may serve to identify which patients will benefit the most from preoperative supplements.…”
Section: Discussionmentioning
confidence: 96%
“…Previous data utilizing preoperative ONS demonstrated benefits on reduction of surgical-site infections in selected weight-losing patients. 53 Again, because many patients do not meet their energy needs from normal food, especially malnourished patients, it is the consensus of this consensus group to encourage the use of high-protein ONS or IMN. As patient compliance with ONS intake (2-3× a day) is essential for benefit, it is vital to emphasize the key role of ONS in preoperative therapy.…”
Section: Preoperative Interventionmentioning
confidence: 99%
“…Patients undergoing esophagectomy have benefited from 5–7 days of nutrition support when compared with controls with reduced postoperative infections, 16 , 17 but other studies have demonstrated no difference with 5–7 days 22 , 23 . Four studies have demonstrated benefit in colorectal patients with varying forms of targeted preoperative nutrition support ranging from 7–10 days 16 , 24 26 . Subgroup analysis in the Jie et al 16 study demonstrated reduced infectious complications in hepatobiliary and pancreatic surgery in patients given 7 days of enteral support vs no therapy.…”
Section: Implementation and Optimizationmentioning
confidence: 99%